Characterization of the submarine disposal of a Bayer effluent (Gardanne alumina plant, southern France): I. Size distribution, chemical composition and settling rate of particles forming at the outfall. (January 2021) - Jacquet, Stéphanie; Monnin, Christophe; Herlory, Olivier; Mille, Deborah; Dufour, Aurélie; Oursel, Benjamin; Heimbürger-Boavida, Lars-Eric; D'onofrio, Sébastien; Layglon, Nicolas; Garnier, Cédric
Abstract: The submarine discharge of the high pH clarified Bayer effluent of the Gardanne alumina plant (Marseille region, France) leads to the formation of concretions at the outfall 324 m underwater and to a plume of white particles. The bulk chemical composition of the concretions has been determined by SF-ICP-MS. Mg and Al are the major elements measured with concentrations of a few hundred mg g −1 . Ca and S are also found at concentrations in the range of mg g −1 . Among the measured trace elements there is a specific interest in As and V because of environmental concerns pointed out by regulation authorities. Their concentrations are of tens to thousands μg g −1, respectively. Concentrations of the other elements are in the range of a few ng g −1 to few hundreds μg g −1 . In order to constrain the dispersion of particles in the environment and to understand how chemical elements can be scavenged from or released to seawater, the size distribution of particles composing the concretions has been measured by settling rate experiments and, for each size class of particles, their chemical composition has been determined. For example, As and V are mainly associated to particles with mean diameters between 15.6 and 63 μm and settling rates around 96 m d −1 . Overall, all the main elements (Mg, Al, Ca, S) composing concretions are associated to this size class of particles which represents 53–60% of the total concretion mass. Highlights: Concretions and particles plume form when the Gardanne effluent mixes with seawater. Particles have mean diameters between 15.6 and 63 μm and settling rates of 96 m d −1 . This size class of particles represents 53–60% of the total concretion mass. Next to Mg, Al, Ca and S, As and V are the main metals found in the particles.